Investigation of Early Planted Winter Canola as a Dual‐Purpose Crop for Silage and Seed Production. (1st September 2015) - Neely, C. B.; Walsh, C.; Davis, J. B.; Hunt, C.; Brown, J.
Abstract : Despite benefits to crop rotations and recent increases in value, the United States produces only a third of the canola ( Brassica napus L.) it consumes. To encourage production expansion, an experiment in Moscow, ID, evaluated dual‐purpose winter canola in a biennial system for forage and seed production. Two winter canola cultivars were sown at three planting densities (4.5, 6.7, and 9.0 kg ha −1 ) over four planting dates (May through September) in 2008, 2009, 2010, and 2011. Vegetative biomass during the first year was harvested and ensiled to determine silage quality. Cultivars performed similarly over all treatments for forage yield and quality. The two highest planting densities yielded more forage, but no seed yield differences were detected. Total dry matter forage yield (DMFY) was greatest for May plantings (5.2 t DM ha −1 ), while August seeded canola yielded 2.4 t DM ha −1 . Baldur produced higher seed yield than Athena by 352 kg ha −1, while planting dates had significant, but inconsistent effects on seed yield compared to the fall‐planted, uncut control, which averaged 2389 kg ha −1 . Fiber content of canola silage (canolage) was extremely low while crude protein (CP) remained consistently high. Canolage quality was exceedingly high, however, high silage pH indicated poor ensiling, which likely led to excessive loss of organic material in the silage that increased ash content. Early‐planted winter canola withstood multiple forage harvests without having a large impact on seed yield most years and economics indicate this may be a feasible management practice.